SIGNIFIKANSI MODIFIKASI AKAD DALAM TRANSAKSI MUAMALAH - Zubair, Muhammad Kamal (IAIN Salatiga, 2010)
The existence of the contract has a crucial role in muamalah field, because there are many implications that appeared. One of them that can be an example that in Islam there is a freedom to conduct the contract by determining the condition or requirements and the form wanted voluntary and not include to the law prohibition. So, the main of contract in Islam is realised the mutual advantages among the contractors.